COVID-19 in an Adult with Down Syndrome: Impact on Autoimmune Response - Hiroshi Kobayashi; Mana Akiniwa; Yoshiko Yamaguchi; Yuji Hirai; Akiko Aoki (Case Reports in Infectious Diseases)
We here report a case of COVID-19 with effusion prior to the development of pneumonia in an adult with Down syndrome. Serositis due to rheumatic disease was initially suspected because of a high titer of serum autoantibodies and leukocytopenia; however, SARS-CoV-2 infection was confirmed by reverse transcription polymerase chain reaction on admission after previous negative tests. Several cases of COVID-19 have been associated with autoimmune responses along with some cases of COVID-19 with autoimmune manifestations. Furthermore, patients with Down syndrome have a higher mortality risk from COVID-19 than the general population, and it is believed that a high sensitivity to the interferon response may contribute to the increased severity of the disease. Thus, careful attention should be paid to autoimmune manifestations due to SARS-CoV-2 infection for ensuring a proper and timely diagnosis, especially in patients with Down syndrome.